The effects of alcohol and marijuana on survival after severe traumatic brain injury: A retrospective cohort study. (September 2020) - Leskovan, John J.; Patel, Puja D.; Pederson, John M.; Moore, Aaron; Afaneh, Amer; Brown, Laura R.
Abstract: Background: Alcohol (ETOH) and marijuana (THC) use have previously shown to improve outcomes after Traumatic Brain Injury (TBI). However, whether TBI severity impacts outcomes among patients tested positive for both ETOH and THC remains unclear. Materials and methods: A retrospective review from the Northern Ohio Regional Trauma Registry, which includes deidentified data from six regional hospitals, including three Level 1 and three Level 3 trauma centers, was performed to assess adult (>18 years) patients with severe TBI (head Abbreviated Injury Score ≥ 3) between January 2012 and December 2018 having an alcohol and drug toxicology screen and data regarding outcome at discharge. Patients were divided into two groups: 1) patients with a negative ETOH and drug test, and 2) patients positive for ETOH + THC. Mortality at discharge was the primary outcome measure and multiple logistic regression was used to assess predictors of mortality at discharge. Results: A total of 854 (median age: 51 years [range: 18–72]; 34.4% female [294/854]) patients were included. On multiple logistic regression, age (p = 0.003), days in intensive care unit (ICU) (p < 0.001), Glasgow Coma Scale (GCS) (p < 0.001), Injury Severity Score (ISS) (p < 0.001), length of stay (LOS) (p < 0.001), and days on ventilator support (p = 0.032) were significant predictors of mortality at discharge. Blood alcohol content (BAC), cause of TBI, drug class, and sex were not significant predictors of mortality at discharge. Conclusions: After severe TBI, positive THC and BAC screening did not predict mortality at discharge after controlling for confounding variables, indicating no survival benefit for patients with severe TBI. Highlights: No survival benefit of alcohol and marijuana for severe traumatic brain injury. Glasgow Coma Scale predict mortality for severe traumatic brain injury. Injury Severity Score predict mortality for severe traumatic brain injury.